Exploiting OTFS frame structure for PAPR reduction - Sümer, Ahmet Sacid; Yılmaz, Talha; Memişoğlu, Ebubekir; Arslan, Hüseyin (Institute of Electrical and Electronics Engineers Inc., 2022)
Wireless technologies have always been the cornerstone of industrial progress. However, as industrial technologies have improved and advanced services have emerged, the demands of industry have meant that wireless technologies have had to adapt. When throughput was the only major concern in previous generations, orthogonal frequency division multiplexing (OFDM) provided an excellent solution for frequency-selective channels. However, the current era of technologies also requires extensive mobility support, resulting in doubly selective channels. As a robust waveform in doubly dispersive channels, orthogonal time-frequency space (OTFS) has been proposed in the literature recently. However, like other multicarrier schemes, OTFS suffers from high a peak-to-average power ratio (PAPR). High PAPR can lead to inter-modulation distortion due to the non-linearity, resulting in severe degradation of detection performance. Therefore, we present a novel PAPR reduction method that exploits the unique OTFS frame structure. Simulation results show that this method can reduce PAPR by up to 2.4 dB, with minimal loss of detection performance compared to conventional OTFS transmission.
Keywords: Delay-Doppler Domain; Multicarrier; OTFS Modulation; PAPR